Involving people with lived experience of homelessness in palliative and end of life care research: key considerations from experts in the field - Jodie Crooks; Kate Flemming; Caroline Shulman; Emma Casey; Briony Hudson (Research Involvement and Engagement, 2024)
Abstract Background Co-production of research aims to include people with lived experience of a phenomena throughout the research process. People experiencing homelessness often experience advance ill-health at a young age, yet access palliative care services at a disparately low rate to the level of palliative care need. The voices of people experiencing homelessness are infrequently heard throughout palliative care research, despite the complexities and intricacies of the area. Aim To explore the experiences of experts in the field to identify key context considerations for involving people with lived experience of homelessness in palliative and end of life care research. Methods Qualitative study comprising two data collection streams: interviews with professionals with experience of involving people experiencing homelessness in their work, and focus groups with people with lived experience (PWLE) of homelessness. Data were analysed using iterative, reflexive thematic analysis. Patient and Public Involvement contributors gave feedback on themes. Results A total of 27 participants took part in semi-structured interviews (N = 16; professionals) or focus groups (N = 11; PWLE homelessness). Key considerations of involving people experiencing homelessness in palliative and end of life care research were developed into four key themes: complexity of lived experience of homelessness; representation of homelessness within experts by experience; professionalising lived experience; and methods for involvement. Conclusions Involvement of people with lived experience of homelessness is important in developing palliative care research. This paper begins to outline some contextual considerations for promoting involvement in a complex and intricate field of research.